![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2/3*x-3/2*x=5/12
x*(2/3-3/2)=5/12
x*(-5/6)=5/12
x=5/12:(-5/6)
x=-1/2
b)2/5+3/5*(3x-3,7)=-53/10
3/5*(3x-3,7)=(-53/10)-2/5=-57/10
(3x-3,7)=(-57/10):3/5=-19/2
3x=(-19/2)+3,7
3x=-29/5
x=(-29/5):3=-29/15
c) 7/9:(2+3/4*x)+5/9=23/27
7/9:(2+3/4*x)=8/27
2+3/4*x=21/8
3/4*x=5/8
x=5/6
k mình nha
a) 2/3.x-3/2.x=5/12
x.(2/3-3/2) =5/12
x.-5/6 =5/12
x =5/12:-5/6
x =1/2
b)2/5+3/5.(3x-3,7)=-53/10
3/5.(3x-3,7)=-53/10-2/5
3/5.(3x-3,7)=-57/10
3x-3,7 =-57/10:3/5
3x-3,7 =-19/2
3x =--19/2+3,7
3x =-29/5
x =-29/5:3
x =29/15
c)7/9:(2+3/4.x)+5/9=23/27
7/9:(2+3/4.x) =23/27-5/9
7/9:(2+3/4.x) =28/27
2+3/4.x =7/9:28/27
2+3/4.x =3/4
3/4.x =3/4-2
3/4.x =-5/4
x =-5/4:3/4
x =-5/3
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 :
a, ( 9/24 + - 18/24 + 14/24 ) . 6/5 + 1/2
= 5/24 . 6/5 + 1/2
= 1/4 + 1/2
= 3/4
b, -3/7 . ( 5/9 + 4/9 ) + 17/7
= - 3/7 . 1 + 17/7
= -3/7 + 17/7
= 14/7
Bài 2 :
a, ( 2/3 + 1/2 ) . x = 5/12
7/6 . x = 5/12
x = 5/12 : 7/6
x = 5/14
b, 14/5 . x - 50 = 51 . 2/3
14/5 . x - 50 = 34
14/5 . x = 34 + 50
14/5 . x = 84
x = 84 : 14/5
x = 30
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x.\left(\frac{2}{3}-\frac{3}{2}\right)=\frac{5}{12}\)
\(\Leftrightarrow x.\left(-\frac{5}{6}\right)=\frac{5}{12}\)
\(\Leftrightarrow x=-\frac{1}{2}\)
b) \(\frac{7}{9}:\left(2+\frac{3}{4}x\right)=\frac{8}{27}\)
\(\Leftrightarrow2+\frac{3}{4}x=\frac{21}{8}\)
\(\Leftrightarrow\frac{3}{4}x=\frac{5}{8}\)
\(\Leftrightarrow x=\frac{5}{6}\)
c) \(\frac{3}{5}.\left(3x-3,7\right)=-\frac{57}{10}\)
\(\Leftrightarrow3x-3,7=-\frac{19}{2}\)
\(\Leftrightarrow3x=-\frac{29}{5}\)
\(\Leftrightarrow x=-\frac{29}{15}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(bai1:a,\frac{3}{7}\cdot\frac{-5}{9}+\frac{4}{9}\cdot\frac{3}{7}-\frac{3}{7}\cdot\frac{8}{9}\)
\(< =>\frac{-15}{63}+\frac{12}{63}-\frac{24}{63}\)
\(< =>\frac{-15+12-24}{63}\)
\(< =>\frac{-3}{7}\)
\(b,1\frac{13}{15}\cdot0,75-\left(\frac{11}{20}+25\%\right):\frac{7}{5}\)
\(< =>\frac{28}{15}\cdot\frac{3}{4}-\left(\frac{11}{20}+\frac{1}{4}\right):\frac{7}{5}\)
\(< =>\frac{7}{5}-\frac{4}{5}:\frac{7}{5}\)
\(< =>\frac{7}{5}-\frac{4}{7}\)
\(< =>\frac{29}{35}\)
\(bai2:\)
\(a,\frac{-3}{4}\cdot x-\frac{4}{10}=\frac{1}{5}\)
\(< =>\frac{-3}{4}\cdot x=\frac{1}{5}+\frac{4}{10}\)
\(< =>\frac{-3}{4}\cdot x=\frac{3}{5}\)
\(< =>x=\frac{3}{5}:\frac{-3}{4}\)
\(< =>x=\frac{-4}{5}\)
\(b,3\left(x-\frac{1}{3}\right)+\frac{1}{3}x=\frac{1}{19}:\frac{12}{19}\)
\(< =>3\left(x-\frac{1}{3}\right)+\frac{1}{3}x=\frac{1}{12}\)
\(< =>\left[3\left(x-\frac{1}{3}\right)\right]=\frac{1}{12}< =>x-\frac{1}{3}=\frac{1}{12}:3=\frac{1}{36}=>x=\frac{1}{36}+\frac{1}{3}=>x=\frac{13}{36}\)
\(< =>\left[\frac{1}{3}\cdot x\right]=\frac{1}{12}< =>x=\frac{1}{12}:\frac{1}{3}=>x=\frac{1}{4}\)
Bài 1:
a)\(\frac{3}{7}.\frac{-5}{9}+\frac{4}{9}.\frac{3}{7}-\frac{3}{7}.\frac{8}{9}\) b,\(1\frac{13}{15}.0,75-\left(\frac{11}{20}+25\%\right):\frac{7}{5}\)
\(=\frac{3}{7}.(\frac{-5}{9}+\frac{4}{9}-\frac{8}{9})\) \(=\frac{28}{15}.\frac{3}{4}-\left(\frac{11}{20}+\frac{5}{20}\right):\frac{7}{5}\)
\(=\frac{3}{7}.\frac{-9}{9}\) \(=\frac{7}{5}-\frac{4}{5}:\frac{7}{5}\)
\(=\frac{-3}{7}\) \(=\frac{7}{5}-\frac{4}{7}\)
\(=\frac{29}{35}\)
Bài 2:
a)\(\frac{-3}{4}x-\frac{4}{10}=\frac{1}{5}\) b,\(3\left(x-\frac{1}{3}\right)+\frac{1}{3}x=\frac{1}{19}:\frac{12}{19}\)
\(\frac{-3}{4}x\) \(=\frac{1}{5}+\frac{4}{10}\) \(3\left(x-\frac{1}{3}\right)+\frac{1}{3}x=\frac{1}{12}\)
\(\frac{-3}{4}x\) \(=\frac{3}{5}\) \(\left(x.3-\frac{1}{3}.3\right)+\frac{1}{3}x=\frac{1}{12}\)
\(x\) \(=\frac{3}{5}:\frac{-3}{4}\) \(\left(x.3-1\right)+\frac{1}{3}x=\frac{1}{12}\)
\(x\) \(=\frac{4}{-5}\) \(x.\left(3+\frac{1}{3}\right)-1=\frac{1}{12}\)
\(x.\left(3+\frac{1}{3}\right)=\frac{1}{12}+1\)
\(x.\frac{10}{3}=\frac{13}{12}\)
\(x=\frac{13}{12}:\frac{10}{3}\)
\(x=\frac{13}{40}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
g) \(\left(x+\frac{1}{2}\right)\left(\frac{2}{3}-2x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+\frac{1}{2}=0\\\frac{2}{3}-2x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{-1}{2}\\x=\frac{1}{3}\end{cases}}\)
Vây \(x\in\left\{\frac{-1}{2};\frac{1}{3}\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\frac{8}{9}x-\frac{2}{3}=\frac{1}{3}x+1\frac{1}{3}\)
\(\Rightarrow\frac{8}{9}x-\frac{1}{3}x=\frac{2}{3}+1\frac{1}{3}\)
\(\Rightarrow\frac{5}{9}x=\frac{2}{3}+\frac{4}{3}\)
\(\Rightarrow\frac{5}{9}x=2\Rightarrow x=2\div\frac{5}{9}=\frac{18}{5}\)
\(b)(\frac{-2}{5}+\frac{3}{7})-(\frac{4}{9}+\frac{12}{20}-\frac{13}{25})+\frac{7}{35}\)
\(=\frac{1}{35}-(\frac{4}{9}+\frac{3}{5}-\frac{13}{25})+\frac{1}{5}\)
\(=\frac{1}{35}-(\frac{4}{9}+\frac{15}{25}-\frac{13}{25})+\frac{1}{5}\)
\(=\frac{1}{35}-(\frac{4}{9}+\frac{2}{25})+\frac{1}{5}\)
\(=\frac{1}{35}-\frac{118}{25}+\frac{1}{5}\)
Làm nốt
\(3\frac{2}{3}-x+\frac{-5}{9}=\frac{5}{12}-\frac{-7}{9}\)
\(\frac{11}{3}-x=\frac{43}{36}-\frac{-5}{9}\)
\(x=\frac{11}{3}-\frac{7}{4}\)
\(x=\frac{23}{12}\)
Chúc bạn học tốt!
\(3\frac{2}{3}-x+-\frac{5}{9}=\frac{5}{12}-\frac{-7}{9}\)
<=> \(\frac{11}{3}-x-\frac{5}{9}=\frac{43}{36}\)
=> x=\(\frac{11}{3}-\frac{5}{9}-\frac{43}{36}=\frac{23}{12}\)